The Effect of Plyometric Training Methods: Hurdle Hops Jump and Box Jump on Leg Muscle Explosive Power and Blocking Skills of Male Volleyball Extracurricular Students at SMK Negeri 4 Bandar Lampung - Wiasta, Made Angga; Tarigan, Herman; Tarigan, Boy Sembaba; Ramadhani, Africo; Lungit Wicaksono; Joan Siswoyo (Jurnal Pendidikan Jasmani (JPJ), 2025)
This study aims to determine the effect of plyometric training methods hurdle hops jump and box jump on lower limb explosive power and blocking skills among male students participating involleyball extracurricular activities at SMK Negeri 4 Bandar Lampung. The research employed acomparative experimental method. The sample consisted of 30 students, divided into two groupsusing the ordinal pairing technique. Data analysis included pre-requisite tests and t-tests. Theresults of the study indicate that: (1) There is a significant effect of the hurdle hops jump trainingon lower limb explosive power, with a calculated t-value of 11.514 > t-table 2.145, and on blockingskills, with a calculated t-value of 17.004 > t-table 2.145. (2) There is a significant effect of thebox jump training on lower limb explosive power, with a calculated t-value of 18.563 > t-table2.145, and on blocking skills, with a t-value of 20.916 > t-table 2.145. (3) There is no significantdifference between the hurdle hops jump and box jump training methods in terms of their effecton lower limb explosive power (t = 0.490 < t-table = 2.048), but there is a significant difference intheir effect on blocking skills, with a t-value of 3.720 > t-table = 2.048, in favor of the box jumpmethod.